A Comparative Study of Olodumare, the Yoruba Supreme Being and the Judea-Christian God - Segun Ogungbemi (Yoruba Studies Review)
This comparative study of Olodumare in Yoruba thought and the Judeo-Christian God reviews the reasons why these two deities from different cultures are so often equated, when they are not necessarily so. This paper uses a philosophical-theological method of inquiry that is apt in giving a concise clarification of theological interface between the two religious and cultural beliefs. It Is not the intention of this paper to argue that the Yoruba concept of 016dumare Is superior to the Christian concept of God. Rather, it is argued that they are not necessarily the same. Finally, the essay establishes that the Yoruba before the advent of Christianity had a philosophical concept of the existence of 016dumare, the Creator of everything that is in the primordial existence and the material world.